Enhancing interlaminar fracture toughness of woven carbon fibre/epoxy composites with engineering thermoplastic and carbon-based nanomaterials. (15th February 2022) - Tangthana-umrung, Kanokporn; Mahmood, Humza; Zhang, Xiaomeng; Gresil, Matthieu
Abstract: Carbon fibre reinforced polymer (CFRP) composites based upon epoxy matrices containing polyethersulfone (PESU) and/or graphene nanoplatelets (GNPs) and/or multi-walled carbon nanotube (MWCNTs) were prepared by hand lay-up without any solvent. The influence of individual and hybrid toughened particles on flexural properties and mode I interlaminar fracture toughness were examined. The maximum value of normalised flexural strength (858 MPa) was measured for CFRP with PESU toughened epoxy. There are no noticeable changes in flexural modulus between all modified laminates. Mode-I interlaminar fracture toughness of crack initiation (G Ic ini ) and crack propagation (G Ic prop ) were enhanced when the matrices of laminates were toughened by whether thermoplastic or carbon-based nanomaterials. The epoxy laminates with 5 %wt PESU and a hybrid ratio of GNP/MWCNT 0.4/0.1 (%wt/%wt) exhibits the greatest G Ic ini (228 J/m 2 ) and excellent G Ic prop (676 J/m 2 ). Surface fracture revealed that this enhancement is due to the simultaneous toughening mechanism of PESU rich particles (crack deviation, crack pinning, debonding), GNPs (crack deviation), and MWCNTs (pull out). This work also evidences that it is important to introduce similar size of tougheners for improving interlaminar toughness of multifunctional CFRP composites.